Formulation and Evaluation of Herbal Neem Anti-Dandruff Shampoo - Khandagale Sandip.S; Supekar Amol.V; Sarukh Vikram.S; Bhasme Prajakta.S; Shaikh Akiburrehman; Shaikh Uwes; Shaikh Fardin (International Journal of Ayurveda and Pharma Research, 2023)
The purpose of this present research work was to formulate and evaluate anti-dandruff shampoo which was prepared from herbal plant Neem leaves and Tulsi. These two plants are major role in formulation of anti-dandruff shampoo with antimicrobial and anti-inflammatory activity. The dandruff is a common disorder which is caused by yeast over growth, there is a fungus which is lives in the scalp of peoples called Malassezia. When a shampoo used under prescribed condition removes skin debris and the dirt from the scalp. Various antifungal and antimicrobial agents or drugs are uses in the preparation of shampoos, which causes the various side effects like hair loss, scratching, discomfort. An attempt to formulate Neem anti-dandruff shampoo which is safer and healthier than other anti-dandruff shampoo’s who are based on the chemicals. Herbal anti-dandruff shampoo formulated by all the herbal ingredients Neem leaves extract as API and anti-dandruff activity, Tulsi leaves which have the anti-microbial activity, Aloe vera which has moisturizing effect etc. The formulated shampoo were passed through evaluation parameter such as visual inspection, foaming capacity pH, viscosity, consistency of foam, etc.